ИЗМЕНЕНИЯ ПАРАМЕТРОВ ПОЛ, МНМ, СММ И ФЕРМЕНТОВ АНТИОКСИДАНТНОЙ СИСТЕМЫ ПРИ ТЯЖЕЛОЙ ПРЕЭКЛАМПСИИ - Чайка, Надежда Алексеевна; Данилова, Любовь Андреевна; Литвиненко, Любовь Александровна (FORCIPE, 2022)